2019
DOI: 10.1137/17m1141047
|View full text |Cite
|
Sign up to set email alerts
|

On the Expansion of Group-Based Lifts

Abstract: A k-lift of an n-vertex base graph G is a graph H on n × k vertices, where each vertex v of G is replaced by k vertices v 1 , · · · , v k and each edge (u, v) in G is replaced by a matching representing a bijection π uv so that the edges of H are of the form (u i , v πuv(i) ). Lifts have been studied as a means to efficiently construct expanders. In this work, we study lifts obtained from groups and group actions. We derive the spectrum of such lifts via the representation theory principles of the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…However, the situation is not that bad if we apply a large shift ℓ-lift only once. As it was shown in Theorem 1.2 from [42], if the base graph Γ has good spectral expansion properties, then by using random shifts the obtained graph Γ also has good expansion properties, even when the lift size ℓ is very large. In [13], such graphs Γ were used to construct quasi-cyclic expander codes of very large lift size ℓ such that the corresponding parity-check matrix H and its transpose H * have good expansion properties.…”
Section: Expander Graphs and Liftsmentioning
confidence: 84%
“…However, the situation is not that bad if we apply a large shift ℓ-lift only once. As it was shown in Theorem 1.2 from [42], if the base graph Γ has good spectral expansion properties, then by using random shifts the obtained graph Γ also has good expansion properties, even when the lift size ℓ is very large. In [13], such graphs Γ were used to construct quasi-cyclic expander codes of very large lift size ℓ such that the corresponding parity-check matrix H and its transpose H * have good expansion properties.…”
Section: Expander Graphs and Liftsmentioning
confidence: 84%
“…Csikvári [6] combined graph covers with graph limit theory to prove the so-called Lower Matching Conjecture of Friedland, Krop and Markström [7]. The properties of random lifts are also widely studied, see for instance the papers [1] and [8].…”
Section: Resultsmentioning
confidence: 99%
“…When one restricts H to be abelian, Agarwal et al [ACKM19] showed that random (Z ℓ , ℓ)-lifts (also known as shift lifts) are expanding. Motivated by the applications of these lifts to codes, we obtain explicit constructions of expanding abelian lifts, for a wide range of lift sizes.…”
Section: Current Techniquesmentioning
confidence: 99%
“…Panteleev and Kalachev use the aforementioned randomized construction of abelian lifted expanders by Agarwal et al [ACKM19], where each edge of the base graph is a associated with an element in Z ℓ sampled uniformly. When ℓ is in the exponential regime they obtain quantum LDPC codes with almost linear distance, i.e., Ω(N/ log(N)).…”
Section: Derandomized Quantum and Classical Codesmentioning
confidence: 99%
See 1 more Smart Citation